Complete Genome Sequence Analysis of Nocardia brasiliensis HUJEG-1 Reveals a Saprobic Lifestyle and the Genes Needed for Human Pathogenesis - Gordon, Stephen V.; Vera Cabrera, Lucio; Ortiz López, Rocío; Elizondo González, Ramiro; Ocampo Candiani, Jorge (Public Library of Science, 2013)
Nocardia brasiliensis is an important etiologic agent of mycetoma. These bacteria live as a saprobe in soil or organic material and enter the tissue via minor trauma. Mycetoma is characterized by tumefaction and the production of fistula and abscesses, with no spontaneous cure. By using mass sequencing, we determined the complete genomic nucleotide sequence of the bacteria. According to our data, the genome is a circular chromosome 9,436,348-bp long with 68% G+C content that encodes 8,414 proteins. We observed orthologs for virulence factors, a higher number of genes involved in lipid biosynthesis and catabolism, and gene clusters for the synthesis of bioactive compounds, such as antibiotics, terpenes, and polyketides. An in silico analysis of the sequence supports the conclusion that the bacteria acquired diverse genes by horizontal transfer from other soil bacteria, even from eukaryotic organisms. The genome composition reflects the evolution of bacteria via the acquisition of a large amount of DNA, which allows it to survive in new ecological niches, including humans.